Pathogenicity and Immunogenicity of a Serially Passaged Attenuated Genotype 2c Porcine Epidemic Diarrhea Virus Cultured in Suspended Vero Cells - Ge, Fei-Fei; Kang, Long-Shan; Shen, Li-Ping; Shen, Hai-Xiao; Yang, De-Quan; Li, Xin; Ju, Hou-Bin; Zhao, Hong-jin; Wang, Jian (Frontiers in Microbiology, 2022)
In this study, one G2c-subtype strain of Porcine epidemic diarrhea virus (PEDV) (SHXX1902 strain) was isolated from clinical samples in a Vero cell suspension, which was different from the genotype of the commercial AJ1102 vaccine. As a result, we determined the pathogenicity of different passages' isolates (SHXX1902 strain) and compared the immunogenicity of G2c-subtype strain (SHXX1902 strain) with the commercial AJ1102 vaccine. The viral titer reached 107 TCID50/mL, which met the requirement for seed virus replication during vaccine development. 5-day-old piglets were orally infected with viruses from passages P5 and P35 to determine the pathogenicity and immunogenicity of different passages. Pregnant sows were immunized with inactivated SHXX1902-P5 or the commercial AJ1102 vaccine (first immunized with an attenuated vaccine and then boosted with an inactivated vaccine) to study the influence of the culture method on the immunogenicity of the strain. The median pig diarrhea dose (PDD50) and the median lethal dose (LD50) of the P5 virus were 102.00 TCID50/mL and 102.84 TCID50/mL, respectively. All five piglets infected with the SHXX1902-P5 virus shed the virus 24 h after vaccination, whereas only two of the five piglets treated with the SHXX1902-P35 virus shed the virus 48 h after vaccination. The SHXX1902-P35 virus was partially attenuated in the 5-day-old piglets. Inactivated SHXX1902-P5 induced PEDV-specific immune- globulin G (IgG) antibody responses equivalent to those induced